Stakeholder perspectives around post-TB wellbeing and care in Kenya and Malawi - Sarah Karanja; Tumaini Malenga; Jessie Mphande; Stephen Bertel Squire; Jeremiah Chakaya Muhwa; Ewan M. Tomeny; Laura Rosu; Stephen Mulupi; Tom Wingfield; Eliya Zulu; Jamilah Meghji (Public Library of Science (PLoS), 2022)
Background There is growing awareness of the burden of post-TB morbidity, and its impact on the lives and livelihoods of TB affected households. However little work has been done to determine how post-TB care might be delivered in a feasible and sustainable way, within existing National TB Programmes (NTPs) and health systems, in low-resource, high TB-burden settings. In this programme of stakeholder engagement around post-TB care, we identified actors with influence and interest in TB care in Kenya and Malawi, including TB-survivors, healthcare providers, policy-makers, researchers and funders, and explored their perspectives on post-TB morbidity and care. Methods Stakeholder mapping was completed to identify actors with interest and influence in TB care services in each country, informed by the study team's local, regional and international networks. Key international TB organisations were included to provide a global perspective. In person or online one-to-one interviews were completed with purposively selected stakeholders. Snowballing was used to expand the network. Data were recorded, transcribed and translated, and a coding frame was derived. Data were coded using NVivo 12 software and were analysed using thematic content analysis. Online workshops were held with stakeholders from Kenya and Malawi to explore areas of uncertainty and validate findings. Results The importance of holistic care for TB patients, which addresses both TB comorbidities and sequelae, was widely recognised by stakeholders. Key challenges to implementation include uncertainty around the burden of post-TB morbidity, leadership of post-TB services, funding constraints, staff and equipment limitations, and the need for improved integration between national TB and non-communicable disease (NCD) programmes for care provision and oversight. There is a need for local data on the burden and distribution of morbidity, evidence-informed clinical guidelines, and pilot data on models of care. Opportunities to learn from existing HIV-NCD services were emphasised. Discussion This work addresses important questions about the practical implementation of post-TB services in two African countries, exploring if, how, where, and for whom these services should be provided, according to a broad range of stakeholders. We have identified strong interest in the provision of holistic care for TB patients in Kenya and Malawi, and key evidence gaps which must be addressed to inform decision making by policy makers, TB programmes, and funders around investment in post-TB services. There is a need for pilot studies of models of integrated TB care, and for cross-learning between countries and from HIV-NCD services.